Does feet position alter triceps surae EMG record during heel-raise exercises in leg press machine? - Pereira, Reginaldo S.; Azevedo, Jônatas B.; Politti, Fabiano; Paunksnis, Marcos R. R.; Evangelista, Alexandre L.; Teixeira, Cauê V. La Scala; Serra, Andrey J.; Alonso, Angelica C.; Pitta, Rafael M.; Júnior, Aylton Figueira; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: muscle activation measured by electromyography (EMG) provides additional insight into functional differences between movements and muscle involvement. Objective: to evaluate the EMG of triceps surae during heel-raise exercise in healthy subjects performed at leg press machine with different feet positions. Methods: ten trained healthy male adults aged between 20 and 30 years voluntarily took part in the study. After biometric analyses the EMG signals were obtained using a 8-channel telemeterized surface EMG system (EMG System do Brazil, Brazil Ltda) (amplifier gain: 1000x, common rejection mode ratio >100 dB, band pass filter: 20 to 500 Hz). All data was acquired and processed using a 16-bit analog to digital converter, with a sampling frequency of 2kHz on the soleus (Sol), medial (GM) and lateral (GL) gastrocnemius muscles in both legs, in accordance with the recommendations of SENIAN. The root mean square (RMS) of the EMG amplitude was calculated to evaluate muscle activity of the three muscles. After being properly prepared for eletromyography procedures, all subjects were instructed to perform 3 sets of 5 repetitions during heel-raise exercise using the maximal load that enabled 10 repetitions on leg press 45° machine, each set being performed with one of the following feet positions: neutral (0º), internal and external rotation (both with 45° from neutral position). The tests were sequential and applied a 5-minute rest interval between sets. The order of the tests was randomized. Results: thought had been found interaction (F=0.27, P= 0.75) on RMS parameters and feet position, the values of Sol muscle were significantly (F=17.86, P= 0.003) lower compared with GL and GM muscles independently of feet position. Conclusion: The change in the feet position during the heel-rise exercise performed in the leg press does not influence the activation of the triceps surae, and the soleus is less activated than the gastrocnemius in that exercise.